STATISTICAL INDICATORS REFLECTING THE EFFECTIVE USE OF INVESTMENTS IN INDUSTRY AND A METHOD FOR THEIR ASSESSMENT (International Congress on Economics, Management and Business Studies, 2026)
In the current conditions of increasing global competition and development in the world, the role of industry in the socio-economic development of the country and in providing the population with decent living conditions is great, and its development is of great importance. Industry accounts for 26.0% of global GDP and 23.1% of total employment [1]. Specifically, this figure is 24.4% in Germany, 37.5% in Norway, 25.2% in Poland, and 28.6% in Kazakhstan [2]. Industry also plays an important role in the socio-economic development of countries, the satisfaction of people's needs for high-tech products, and the growth of the state's export potential.